Printed Flexible Heaters‐Based Thermotherapy Platform for Multiduty Thermal Management. Issue 8 (5th June 2020) - Liu, Qun; Tian, Bin; Luo, Chengsheng; Liang, Jing; Wu, Wei
Abstract: Printed flexible heaters (FHs) with excellent heating performance and thermal stability are quite desirable for the development of portable thermotherapy platform. Herein, the facile screen‐printing technology is used to fabricate the highly oxidation‐resistant Cu @ Ni rose‐stem nanowires (RSNWs) ‐ based low‐cost scalable FHs. The Cu @ Ni RSNWs possess low sheet resistance of 1.9 Ω sq −1 after low temperature sintering (90 °C). The FHs not only exhibit great oxidation resistance (almost no change at 180 °C for 30 min), but also maintain the great conductivity (Δ R / R 0 < 0.3) even after being exposed to ambient atmosphere for 60 days. Furthermore, the FHs exhibit great heating performance with the saturation temperature of 172.8 °C under 6 V, and can keep stable heating cycles for 5500 s under both parameters of the stepwise‐rising voltage from 2 to 6 V and consistent load‐on voltage of 6 V. In addition, the heaters array can greatly shorten the time of raising the temperature of the blood bag from 5 to 20 °C. The outstanding heating performance of the FHs provides great chances for portable variable‐area flexible heating platform in the field of multiduty thermal management. Abstract : The facile screen‐printing technology is used to fabricate the Cu@Ni rose‐stem nanowires‐based flexible heaters (FHs) with excellent heating performance. The heating wristband (13 mm × 110 mm) and large‐area heaters array (75 mm × 100 mm) assembled with several FHs exhibit the great thermal stability and portability, indicating excellent potential in the field of multiduty thermal management